Joint pricing and replenishment policies for group-buying auction. (1st January 2014) - Tai, Allen H.
Group-buying auction has become a popular marketing strategy in the last decade. In this paper, a stochastic model is developed for an inventory system subjects to price-sensitive demand from group-buying auctions. The model discussed here takes into account the costs of inventory, transportation, dispatching and re-order as well as the penalty cost of non-successful auctions. Since a new cycle begins whenever there is a replenishment of products, the long-run average profit can be obtained by using the renewal theory. Closed form solution of the optimal replenishment quantity is derived and an optimal unit selling price is then obtained.